2013
DOI: 10.4028/www.scientific.net/amm.315.670
|View full text |Cite
|
Sign up to set email alerts
|

Mercerization Treatment Conditions Effects on Kenaf Fiber Bundles Mean Diameter Variability

Abstract: The interest in utilizing natural fiber as reinforce in polymer composites has increased in recent years due to their advantages like availability, cheap, renewable, lightweight, and biodegradable. However, the main challenge of natural fiber to be used as reinforcement in polymer is their hydrophobic nature. One of the solutions is via chemical modification like mercerization treatment. In this study, the effect of alkali concentrations at 2 and 10 w/v %; and soaking temperature at 30°C and 80°C on a kenaf fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…They concluded that the tensile strength of kenaf fiber decreased by increasing the alkali solution concentration and immersion time. This finding was good agreement with previously conducted studied by Hashim [7]. He used different alkali treatment conditions setting and found that alkali concentration had a higher impact on diameter changes compared to alkali treatment immersion temperature.…”
Section: Introductionsupporting
confidence: 92%
“…They concluded that the tensile strength of kenaf fiber decreased by increasing the alkali solution concentration and immersion time. This finding was good agreement with previously conducted studied by Hashim [7]. He used different alkali treatment conditions setting and found that alkali concentration had a higher impact on diameter changes compared to alkali treatment immersion temperature.…”
Section: Introductionsupporting
confidence: 92%
“…This finding could be explained by the more effective leaching of non‐cellulosic materials, fiber degradation and fiber delignification phenomenon that occurred with kenaf fiber as alkali treatment variables increased . The main results of kenaf fibers reveal that alkali concentration had a higher impact on mean diameter changes than soaking temperature . In our study with açaí fiber, the alkali concentration also played a more important role in fiber diameter changes than the reaction temperature.…”
Section: Resultsmentioning
confidence: 52%
“…[23] The main results of kenaf fibers reveal that alkali concentration had a higher impact on mean diameter changes than soaking temperature. [24] In our study with açaí fiber, the alkali concentration also played a more important role in fiber diameter changes than the reaction temperature.…”
Section: Scanningmentioning
confidence: 63%
“…This treatment improves the fiber surface adhesive characteristic by removing any hemicellulose and wax on the fiber surface, and increasing surface contact between the defibrillation fibers and the matrices . In addition, the monoclinic crystalline lattice of cellulose‐I can be changed into a more thermally stable cellulose‐II crystalline structure after alkalization . Edeerozey et al found that the immersion of the KF in a 6% NaOH concentration solution for 3 h effectively cleaned the fiber surface and increased the tensile strength of the KF.…”
Section: Introductionmentioning
confidence: 99%